Diversidad y similaridad de arvenses en plantaciones forestales de Gmelina arborea Roxb. (melina) en la zona central del Litoral Ecuatoriano. - Jiménez Ordoñez, Nathaly Esthefanía (2021)
This research was carried out at seven sites on the Ecuadorian Littoral. The main objective was to assess the diversity and similarity of Arvenses in Gmelina arborea Roxb forest plantations. (melina). 24 UM of 256 m2 was established using the minimum area method. In each sampling unit they recorded scientific name, morphology, number of individuals per species. It calculated abundance, frequency, density, IVI, Jaccard index, Simpson Shannon. Cluster analysis was performed at all seven study sites resulting in the composition of 5 clusters, an ANOVA, Tukey test, and t-Student test were performed. With a total of 21649 individuals, 155 species, 37 indeterminate, 107 genera, 64 families in the 24 sampling units. The most representative families were Compositae and Poaceae, the species with the greatest abundance and IVI was Rottboellia cochinchinensis, the most commonly Phyllanthus niruri and Piper aduncum. The species, Rottboellia cochinchinensis presented higher density. The sites of Yurac Yacu 2012 and Toachi 2013 obtained the greatest similarity. In all seven places, an average diversity was achieved according to Simpson and Shannon. The ANOVA analysis presented statistically significant differences at the seven sites, with p-0.0006095 < to 0.05 to 95%, the t-test based on the similarity and diversity parameters evaluated to the sites, if there are significant differences. According to the results, the alternative hypothesis is accepted that there is diversity and similarity of Arvenses in the plantations of G. arborea at the sites La Palma 2015, Yurac Yacu 2012 and Toachi 2013 being close to the foothills of the mountain range because they are wetter areas.